Realigning the Union Budget to Myanmar’s Development Priorities : Myanmar Public Expenditure Review 2015 - World Bank (World Bank, Washington, DC, 2016)
Union Budget policies in Myanmar have undergone fundamental shifts since 2011 to accelerate delivery of essential public services. This first ever Public Expenditure Review (PER) for Myanmar tries to better understand these shifts and recommend ways to further align budget policies to development priorities. The Myanmar PER 2015 is divided into five parts: (i) sustainability of aggregate fiscal policy; (ii) rebalancing the composition of the Union Budget; (iii) improving coverage, quality and equity of education services; (iv) going from more to better government spending on health; and (v) a sound fiscal framework for sub-national service delivery. The book is arranged as follws: (i) chapter one starts with introduction; (ii) chapter two deals with sustainability of aggregate fiscal policy; (iii) chapter three focuses on rebalancing the composition of the union budget; (iv) chapter four deals with improving the coverage, quality and equity of education; (v) chapter five suggests from more to better government spending on health; and (vi) chapter six talks about fiscal framework for sub-national service delivery.